PENGARUH KUALITAS PRODUK, KUALITAS PELAYANAN, DAN ETIKA BISNIS ISLAM TERHADAP KEPUASAN KONSUMEN PADA UMKM ENDERESE DI DESA BARENG - Rica Wahyuningsih; Agus Eko Sujianto (STIE 'INDONESIA' Pontianak, 2022)
The goal of this study is to determine how product quality, service quality, and Islamic business ethics influence consumer satisfaction at Enderese SMEs in Bareng Village. This study employs both an associative and a quantitative approach. The researcher used a non-probability sampling technique because he did not know the total number of members of the population studied. The accidential sampling method is used in sampling. As a sample, there are 35 respondents. As a data collection tool, a questionnaire is used. Data analysis techniques and multiple linear regression analysis techniques are used. According to the study's findings, product quality, service quality, and Islamic business ethics all have a significant impact and a positive relationship on consumer satisfaction